FLY ASH MIXING WITH MINE OB DUMPS: AN ENVIRO-FRIENDLY, CLEAN AND GREEN METHOD OF DISPOSAL - Dewangan, P; Lokhande, R; Agarwal, A; Patel, R; Bhargav, H (MATTER: International Journal of Science and Technology, 2017)
Fly ash generation, its utilization and safe disposal is a major problem faced by thermal power plants (TPP) in India. Despite several efforts of the government, the utilization of fly ash is reached to only 55% of the total fly ash generated and remaining 45% fly ash is still being dumped into poorly designed and maintained ash ponds. At present, fly ash is mainly being utilized for making cement, bricks, concrete, roads and small quantity in mine void filling. The consumption of fly ash in construction activity has reached to almost saturation level and there is not much potential to consume more fly ash in these segments. Mine void filling is the only potential area where bulk quantity of fly ash can be utilized and 100% utilization target can be achieved. This paper investigates the suitability of fly ash to be disposed off by mixing it with overburden (OB) dumps in coal mines. Characterization of both the OB dump material and fly ash were carried out in the laboratory. The compaction and shear tests were performed on OB dump material and the same mixed with 25% fly ash by volume as per the guidelines issued by Ministry of Environment Forest and Climate Change, Govt. of India. The stability condition of both OB dump and fly ash mixed OB dump at varying slope angles were analyzed using FLAC 3D slope stability software and dump angle were optimized for safe disposal of the fly ash.